Biodegradation Test of Rhodamine B by Mangrove Root Symbiont Bacteria Avicennia marina in Sea Panipahan, Muara Rokan, Panipahan Village, Riau - Annisa, Rizka; Rasyidah, Rasyidah; Mayasari, Ulfayani (Universitas Sultan Ageng Tirtayasa, 2024)
Rhodamine B is a major problem that arises as a result of the development of the textile industry. Rhodamine B is known to be difficult to degrade naturally thus causing a lot of damage, both to the environment and human health such as respiratory tract infection, skin irritation, digestive tract irritation, and eye infection. This study aims to find and determine the type of mangrove root symbiont bacteria Avicennia marina from Panipahan Village that can degrade Rhodamine B. This research is divided into several stages, namely sampling, isolation, purification, characterization of colony morphology, Rhodamine B biodegradation test through the overlay method, gram staining, biochemical tests, and molecular tests to determine the type of bacteria. The results obtained 16 isolates of symbiont bacteria that were successfully isolated from the roots of the Avicennia marina mangrove in Panipahan Village. Of the 16 isolates of symbiont bacteria, only 2 isolates have the potential to degrade Rhodamine B. The results of the biochemical activity test showed positive results in the Catalase, TSIA, motility, and O/F tests on RA5 symbiont bacterial isolates, while the citrate test showed negative results. For RA16 symbiont bacterial isolates, it is known that only the O/F test shows positive results, while the catalase, TSIA, citrate, and motility tests show negative results. The results of bacterial characteristics obtained are that the RA5 symbiont bacterial isolate belongs to the Bacillus circulans type and the RA16 symbiont bacterial isolate belongs to the Bacillus insolitus type. So, it was concluded that there were 2 bacterial isolates of Avicennia marina mangrove root symbionts in Panipahan Village, Riau that were able to degrade Rhodamine B.